A study of noise in a vehicle compartment - 465669 Shamarol Idha Marso @ Samiran; Che Abas Che Ismail, supervisor; Fakulti Kejuruteraan Mekanikal (2007)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2007